Dynamics of m6A RNA Methylome on the Hallmarks of Hepatocellular Carcinoma - Sivasudhan, Enakshi; Blake, Neil; Lu, Zhi-Liang; Meng, Jia; Rong, Rong (Frontiers in Cell and Developmental Biology, 2021)
Epidemiological data consistently ranks hepatocellular carcinoma as one of the leading causes of cancer-related deaths worldwide, often posing severe economic burden on healthcare. While the molecular etiopathogenesis associated with genetic and epigenetic modifications has been extensively explored, the biological influence of the emerging field of epitranscriptomics and its associated aberrant RNA modifications on tumorigenesis is a largely unexplored territory with immense potential for discovering new therapeutic approaches. In particular, the underlying cellular mechanisms of different hallmarks of hepatocarcinogenesis that are governed by the complex dynamics of m6A RNA methylation demand further investigation. In this review, we reveal the up-to-date knowledge on the mechanistic and functional link between m6A RNA methylation and pathogenesis of hepatocellular carcinoma.